2009
DOI: 10.1007/s10163-009-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sodium on biohydrogen production from food waste by anaerobic fermentation

Abstract: Anaerobic fermentation of food waste for hydrogen production was performed in serum bottles with various linear alkylbenzene sulfonate (LAS) dosages (7.1-21.4 g/l) and sodium concentrations (5.03-28.7 g/l). LAS can effectively inhibit the activity of hydrogen-consuming bacteria, and the maximum hydrogen yield of 109.2 ml/g volatile solid (VS) was obtained at an LAS dosage of 14.3 g/l without added sodium. The feasible pH for hydrogen production is 5.0-6.0, and the process will slow down or stop when the pH is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…While at above optimal levels the hydrogen producing capability is severely compromised due to its effect on the microbial enzyme activities such as dehydrogenase activity, alkaline phosphatase and ATP (Hao et al, 2006). This finding is compatible with Hao et al (2006) and Cao and Zhao (2009) who have reported the positive effect of sodium ion concentration on hydrogen production from sucrose using anaerobic hydrogen producing granular sludge. However, this finding is against the report of Alshiyab et al (2008) that sodium ions are totally detrimental to the hydrogen producing capacity of organisms.…”
Section: Effect Of Sodium Ions On Hydrogen Productionsupporting
confidence: 86%
“…While at above optimal levels the hydrogen producing capability is severely compromised due to its effect on the microbial enzyme activities such as dehydrogenase activity, alkaline phosphatase and ATP (Hao et al, 2006). This finding is compatible with Hao et al (2006) and Cao and Zhao (2009) who have reported the positive effect of sodium ion concentration on hydrogen production from sucrose using anaerobic hydrogen producing granular sludge. However, this finding is against the report of Alshiyab et al (2008) that sodium ions are totally detrimental to the hydrogen producing capacity of organisms.…”
Section: Effect Of Sodium Ions On Hydrogen Productionsupporting
confidence: 86%
“…The first observation is that, in several studies that had claimed high hydrogen yields at higher temperatures, the net energy gain is negative. The second observation is that, the net energy gain found in this study is higher than that estimated from the data reported in all the 16 literature studies, all of which had been conducted at temperatures greater than 35 C. This comparison confirms the premise of this study that net energy gain rather than [13] Food/sewage sludge 35 56.6 À0.08 Cui et al [14] Beer lees waste 35 53.0 0.91 Cao and Zhao [15] Food waste 36 145.5 1.05 Cai et al [16] Sewage sludge 36 16.6 À9.47 Xing et al [17] Dairy manure 36 27.5 À0.37 Fan et al [18] Beer lees waste 36 54.4 0.88 Zhang et al [19] Corn stalk waste 37 130.9 0.48 Lay et al [20] Municipal solid waste 37 2.9 0.00 Danko et al [21] Food waste 37 157.0 2.93 Fang et al [22] Rice slurry 37 346.0 1.20 Pattra et al [23] Sugarcane bagasse 37 44.3 0.68 Feng et al [24] Apple pomace 37 101.1 À0.45 Kim et al [25] Food waste 40 2.7 À0.04 Gilroyed et al [26] Feedlot cattle manure 52 65.0 À0.81 Yokoyama et al [27] Cow waste slurry 60 22.1 À7.80 Luo et al [28] Cassava stillage 60 50.4 À0.68…”
Section: 5supporting
confidence: 89%
“…In this case, alternative metabolites such as lactate are produced instead of hydrogen [31,64]. In particular, Cao and Zhao [65] found an inhibitory threshold level of 14,410 mg/L. Calcium is a constituent of extracellular polysaccharides, which plays a key role in the formation of biofilms and thereby improves cell granulation and settleability [66].…”
Section: Analytical Characterization Of Fw and Inoculamentioning
confidence: 99%